2012
DOI: 10.1152/ajprenal.00261.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bladder smooth muscle organ culture preparation maintains the contractile phenotype

Abstract: Smooth muscle cells, when subjected to culture, modulate from a contractile to a secretory phenotype. This has hampered the use of cell culture for molecular techniques to study the regulation of smooth muscle biology. The goal of this study was to develop a new organ culture model of bladder smooth muscle (BSM) that would maintain the contractile phenotype and aid in the study of BSM biology. Our results showed that strips of BSM subjected to up to 9 days of organ culture maintained their contractile phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…For embryonic mouse bladder smooth muscle, we confirmed that MYPT1 T852 and CPI-17 are phosphorylated by K + depolarization or muscarinic receptor stimulation, which could be reduced by ROCK and PKC inhibitors, respectively. The constitutive MYPT1 T694 phosphorylation was not inhibited by ROCK or PKC inhibitors, similar to other reports for bladder smooth muscle (Wang et al 2009(Wang et al , 2012. Additionally, treatment of bladder tissues with calyculin A did not further increase MYPT1 T694 phosphorylation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For embryonic mouse bladder smooth muscle, we confirmed that MYPT1 T852 and CPI-17 are phosphorylated by K + depolarization or muscarinic receptor stimulation, which could be reduced by ROCK and PKC inhibitors, respectively. The constitutive MYPT1 T694 phosphorylation was not inhibited by ROCK or PKC inhibitors, similar to other reports for bladder smooth muscle (Wang et al 2009(Wang et al , 2012. Additionally, treatment of bladder tissues with calyculin A did not further increase MYPT1 T694 phosphorylation.…”
Section: Discussionsupporting
confidence: 90%
“…The constitutive MYPT1 T694 phosphorylation was not inhibited by ROCK or PKC inhibitors, similar to other reports for bladder smooth muscle (Wang et al . , ). Additionally, treatment of bladder tissues with calyculin A did not further increase MYPT1 T694 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that phosphorylation of Thr696 was more stable compared with that of Thr853, and it may facilitate Thr853 phosphorylation. However, investigations from Chen et al [25] indicated that MYPT1 T852 and CPI-17 are phosphorylated by muscarinic receptor stimulation, which could be reduced by ROCK and PKC inhibitors respectively, and that most MYPT1 Thr694 was phosphorylated constitutively, similar to other reports for bladder smooth muscle [15,26]. So even in studies using the same smooth muscle preparation, the results can vary depending on the laboratory reporting the findings.…”
Section: Discussionmentioning
confidence: 56%
“…The bladder neck, trigone, base region, the urothelium, and submucosa were removed and the bladders were divided in the midsagittal plane, and cut into longitudinal strips. The bladders were cut into longitudinal strips approximately 2 mm wide and 4‐5 mm long and the muscle strips were prepared for adenovirus transduction as described previously . Briefly, the strips were mounted onto polymerized silicone elastomer (Dow Corning, Midland, MI, USA) using 0.1 mm stainless pins.…”
Section: Methodsmentioning
confidence: 99%
“…The bladders were cut into longitudinal strips approximately 2 mm wide and 4-5 mm long and the muscle strips were prepared for adenovirus transduction as described previously. 26 Briefly, the strips were mounted onto polymerized silicone elastomer (Dow Corning, Midland, MI, USA) using 0.1 mm stainless pins. The pins were positioned such that the strips were slightly stretched longitudinally, while raised 2-3 mm above the surface of the elastomer.…”
Section: Bsm Tissue Preparation and Transduction With Adenovirusmentioning
confidence: 99%